The inclusive practices of classroom teachers: a scoping review and thematic analysis - Finkelstein, Simon; Sharma, Umesh; Furlonger, Brett (International journal of inclusive education, 2021)
There is a consensus that what teachers do in the classroom directly impacts student's learning. Currently, however there is a paucity of data identifying which teaching practices actually support learning within an inclusive classroom, especially data derived from direct observations of teachers. Thus, research-based guidance regarding how best to target observations of inclusive teachers warrants further investigation. The purpose of this scoping review, therefore, was to determine which teacher practices are related to high-quality inclusion, when conducting classroom observations. Extracted data from the tools that relied on direct observation methods included concepts and definitions of inclusion, as well as all indicators of inclusive practice. Thematic Analysis of observable inclusive teacher practices were concentrated into five themes: 'Collaboration and Teamwork', 'Determining Progress', 'Instructional Support', 'Organisational Practices', 'Social/Emotional/Behavioural Support'. These themes were used to create a 'guide' for conducting in-class observation of inclusive teachers. Implications for the use of this 'guide' and teacher education are discussed.